INTERVENSI EDUKASI DENGAN MEDIA LEAFLET (SELF- CARE) PADA PASIEN DIABETES MELITUS TIPE II DI WILAYAH KERJA PUSKESMAS PAMPANG - Salmawati Labelo; Akbar Asfar; Andi Mappanganro; Brajakson Siokal (CV. ADIBA AISHA AMIRA, 2025)
Type II Diabetes Mellitus is a chronic disease that remains a major global and national health issue due to its potential to cause serious complications such as heart disease, kidney failure, and neuropathy. The increasing number of cases, including in the working area of Pampang Health Center, highlights the importance of nursing interventions focused on self care. Self-care is an essential strategy to control blood glucose levels through proper diet, physical activity, medication adherence, and regular monitoring. One of the effective educational methods applied is leaflet media, as it is simple, easy to understand, and can be read repeatedly. This study aimed to determine the effectiveness of educational interventions using leaflet media on self-care ability in patients with type II diabetes mellitus. The results showed a decrease in blood glucose levels from 236 mg/dL on the first day to 222 mg/dL on the third day after the education was provided. Furthermore, patient compliance improved in terms of maintaining a healthy diet, engaging in physical activity, and taking prescribed medications. These findings indicate that self-care education using leaflet media positively contributes to enhancing patients’ knowledge, attitudes, and practices in managing diabetes. In conclusion, educational interventions using leaflets are effective in improving self-care and reducing blood glucose levels among type II diabetes mellitus patients, making it a valuable nursing strategy in community health effort for diabetes management.